That's my hand! Activity in premotor cortex reflects feeling of ownership of a limb. - Ehrsson, H; Spence, C; Passingham, R (2004)
When we look at our hands, we immediately know that they are part of our own body. This feeling of ownership of our limbs is a fundamental aspect of self-consciousness. We have studied the neuronal counterparts of this experience. A perceptual illusion was used to manipulate feelings of ownership of a rubber hand presented in front of healthy subjects while brain activity was measured by functional magnetic resonance imaging. The neural activity in the premotor cortex reflected the feeling of ownership of the hand. This suggests that multisensory integration in the premotor cortex provides a mechanism for bodily self-attribution.